Pemanfaatan Teknologi Digital Dalam Proses Pembelajaran di Sekolah Dasar - Hoirunnisa Siregar; Elia Salama; Shiren Saleha Daulay; Rustam Efendi Simatupang; Wenny Lestari; Rika Hasibuan; Nur Ipla Hasibuan; Nurhayati Siregar (Kampus Akademik Publiser, 2026)
This study aims to analyze and describe the utilization of digital technology in the learning process at elementary schools and its contribution to improving learning effectiveness. The study employed a qualitative approach using field research with a socio-legal orientation. Data were collected through observation, in-depth interviews, and documentation, with the researcher serving as the main instrument in the data collection and analysis processes. The data were analyzed descriptively to identify meanings, patterns, and descriptions of digital technology implementation in learning activities. The findings indicate that the use of digital technology through educational applications, interactive videos, online learning platforms, multimedia, and game-based media can improve student engagement, motivation, flexibility, and learning experiences. Digital technology also supports the development of digital literacy, creativity, communication, collaboration, and critical thinking skills. However, its effectiveness is influenced by infrastructure availability, internet stability, teacher competence, and school readiness. Therefore, planned strategies, continuous teacher training, and adequate facilities are needed to ensure optimal and sustainable digital technology integration in elementary school learning.